THE QUALITY OF THE AIS DECISION MAKING PROCESS AND ITS EFFECTIVENESS IN USE OF THE ERPS - Saurabh Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Indonesia has shown significant growth with the use of Enterprise Resource Planning Systems (ERPS) in Indonesia. This increase has led to the need for empirical evidence of the accounting benefits of these systems. The development of ERPS accounting study has provided a great possibility in decision making processes related to the extent of use of the ERPS for further work on the Accounting Information Systems (AIS) consistency and effectiveness. This research uses other Partial Least Square (PLS) approaches. The results show that the AIS quality evaluation by the manager impacts the decision-making process performance. The degree to which ERPS is used can be moderating in the relationship between the management’s understanding of the AIS standard and the reliability of decision-making. Finally, there was no difference between the perceived quality of AIS and the efficacy of the decision-making process on the basis of use of the ERPS of various department managers.